Technology applied in the operation and detection of antipersonnel mines: state of the art - Ledezma-Ríos, Javier Andrés (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
The main objective of this investigation is to know the different technologies implemented for the detection of antipersonnel mines, documented by different bibliographic means of the latest updates used for the detection of buried objects, the factors that affect the loss of energy of the waves as transmitters of information between them, the characteristics of the soil, the amplitude of the emitted signal, the frequency and the conditions of the terrain. This paper informs about the computational means, of their work with the different algorithms to model correct information of what is happening with the phenomenon of detection. Thus, through this research, the scientific community is informed on the parameters of magnetic susceptibility, the percentage of water and porosity of the environment where the emitted waves react, the difficulty of the stability of the signal to be captured to detect antipersonnel mines, in a geographical context. Currently, PVC tubes, cans, syringes and hand-held devices are being used for their production, and the waves will behave differently against these materials.